Sri Lanka’s New Fertilizer Cash Grant (FCG) Scheme for paddy: What do participants and associates look and hope for? - Kopiyawattage, Kumudu; Weerahewa, Jeevika; Roy, Devesh (International Food Policy Research Institute, 2024)
Since independence, the Government of Sri Lanka has implemented various policies and initiatives to boost agricultural production. One of the enduring, costly, and politically sensitive measures aimed at promoting paddy farming has been the fertilizer subsidy program which was initiated in 1962 and continued for over six decades. Since then, the subsidy policy has undergone many changes, including the introduction of the Fertilizer Cash Grant (FCG) Program in 2016. The FCG program's key objectives were to reduce the excessive use of synthetic fertilizers, promote the adoption of organic fertilizers, and empower farmers to make informed decisions regarding the use of fertilizers in appropriate quantities in their fields post soil testing. The FCG program commenced in 2016 but it lasted only for four seasons and price subsidy was reintroduced.